Pelatihan Pembuatan Media Pembelajaran Interaktif Berbasis Canva dan PowerPoint untuk Guru Pendidikan Agama Islam (PAI): Di KKG Banyuates Sampang-Madura: Pelatihan Pembuatan Media Pembelajaran Interaktif Berbasis Canva Dan Powerpoint Untuk Guru Pendidikan Agama Islam (PAI): Di KKG Banyuates Sampang-Madura - Iman Rasiman (Sekolah Tinggi Agama Islam Al-Muntahy, 2025)
This study focuses on the Training on Developing Interactive Learning Media Using Canva and PowerPoint for Islamic Education Teachers (PAI), aiming to enhance teachers’ abilities in designing creative, effective, and contextual digital learning materials. The background of this research stems from the low utilization of digital technology among Islamic Education teachers in classroom instruction, despite the great potential of interactive media to improve student engagement and understanding. The study employs a qualitative approach with a case study design, involving Islamic Education teachers as the primary participants. Data were collected through in-depth interviews, participatory observations, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña (2018), which includes data reduction, data display, and conclusion drawing and verification. The findings reveal that the training effectively enhanced teachers’ pedagogical competence and digital literacy. Participants demonstrated improved ability to integrate technology into Islamic learning by designing interactive media using Canva and PowerPoint, resulting in increased student motivation, engagement, and participation. Furthermore, the study found a paradigm shift among teachers from traditional learning methods toward innovative, student-centered digital learning approaches. The implications of this research highlight the importance of continuous professional development programs for Islamic Education teachers to strengthen the integration of technology in teaching practices, aligning with the demands of the Merdeka Curriculum and the digital era.